Comparing the Effectiveness of Conventional and Microsurgical Access Flap Techniques in Managing Horizontal Bony Defects in Chronic Periodontitis Patients: A Clinical and Radiographic Study - Thakur, Shambhavi; Martande, Santosh; Ankit, Kumar; Gopalakrishnan, D.; Kulloli, Anita; Shetty, Sharath; Mehta, Vini; Suryawanshi, Krishna (European Journal of General Dentistry, 2023)
Objective Periodontal microsurgery is descendant of conventional periodontal surgery to reduce surgical trauma, improve wound healing, and enhance patient compliance. This study compared the efficacy of conventional and microsurgical access flap in the management of horizontal bony defects in chronic periodontitis patients.Materials and Methods Eight pairs of contralateral horizontal bone defects in chronic periodontitis patients were randomly allocated to control group and test group. Microsurgical access flap was carried out in test group under magnification, while control group received conventional access flap. Plaque index (PI), gingival index (GI), probing pocket depth (PPD), relative attachment level (RAL), and relative gingival marginal level (RGML) were recorded at baseline, 3 months, and 6 months. Wound healing index (WHI) was evaluated after 1 week, 2 weeks, and 4 weeks. Pain perception was evaluated using visual analog scale (VAS) post-surgery and after 24 hours. Radiographic defect depth was measured at baseline and after 6 months.Statistical Analysis The statistical analysis was done by SPSS statistical software. The intragroup comparison was done by repeated measures analysis of variance. The intergroup difference between both groups was done by Student's t-test. The descriptive statistics for VAS and WHI was done by Wilcoxon signed rank test. The mean difference between clinical parameters from baseline to follow-up intervals was calculated by post-hoc least significance difference analysis.Results There was significant reduction in PI, GI, PPD, and RAL within both the groups (p < 0.05). There was increase in RGML within both the groups from baseline to 6 months (p < 0.05). In the intergroup comparison, test group showed better WHI and better pain perception (VAS) compared to control group (p < 0.05). No difference was found between both the groups in terms of radiographic defect depth (p > 0.5).Conclusion Both the procedures were effective in improving the clinical parameters but the microsurgical group showed better results in terms of wound healing and less postoperative pain. Both procedures showed no significant effect on radiographic defect depth.
Keywords: chronic periodontitis; horizontal bone defects; conventional access flap; periodontal microsurgery; dental loupes